Case report: Expanding the phenotype of FOXP1-related intellectual disability syndrome and hyperkinetic movement disorder in differential diagnosis with epileptic seizures - Cesaroni, Carlo Alberto; Pollazzon, Marzia; Mancini, Cecilia; Rizzi, Susanna; Cappelletti, Camilla; Pizzi, Simone; Frattini, Daniele; Spagnoli, Carlotta; Caraffi, Stefano Giuseppe; Zuntini, Roberta; Trimarchi, Gabriele; Niceta, Marcello; et al. (Frontiers in Neurology, 2023)
Objective We aimed to report on previously unappreciated clinical features associated with FOXP1-related intellectual disability (ID) syndrome, a rare neurodevelopmental disorder characterized by global developmental delay, intellectual disability, and language delay, with or without autistic features. Methods We performed whole-exome sequencing (WES) to molecularly characterize an individual presenting with ID, epilepsy, autism spectrum disorder, behavioral problems, and facial dysmorphisms as major features. Results WES allowed us to identify a previously unreported de novo splice site variant, c.1429-1G>T (NM_032682.6), in the FOXP1 gene (OMIM*605515) as the causative event underlying the phenotype. Clinical reassessment of the patient and revision of the literature allowed us to refine the phenotype associated with FOXP1 haploinsufficiency, including hyperkinetic movement disorder and flat angiomas as associated features. Interestingly, the patient also has an asymmetric face and choanal atresia and a novel de novo variant of the CHD7 gene. Conclusion We suggest that FOXP1-related ID syndrome may also predispose to the development of hyperkinetic movement disorders and flat angiomas. These features could therefore require specific management of this condition.